Clostridioides difficile minimal nutrient requirements for flagellar motility - Schwanbeck, Julian; Oehmig, Ines; Groß, Uwe; Bohne, Wolfgang (Frontiers in Microbiology, 2023)
As many gastro-intestinal pathogens, the majority of Clostridioides difficile strains express flagella together with a complete chemotaxis system. The resulting swimming motility is likely contributing to the colonization success of this important pathogen. In contrast to the well investigated general energy metabolism of C. difficile, little is known about the metabolic requirements for maintaining the ion motive force across the membrane, which in turn powers the flagellar motor. We studied here systematically the effect of various amino acids and carbohydrates on the swimming velocity of C. difficile using video microscopy in conjunction with a software based quantification of the swimming speed. Removal of individual amino acids from the medium identified proline and cysteine as the most important amino acids that power swimming motility. Glycine, which is as proline one of the few amino acids that are reduced in Stickland reactions, was not critical for swimming motility. This suggests that the ion motive force that powers the flagellar motor, is critically depending on proline reduction. A maximal and stable swimming motility was achieved with only four compounds, including the amino acids proline, cysteine and isoleucine together with a single, but interchangeable carbohydrate source such as glucose, succinate, mannose, ribose, pyruvate, trehalose or ethanolamine. We expect that that the identified defined “minimal motility medium” will be useful in future investigations on the flagellar motility and chemotactic behaviour in C. difficile, particularly for the unambiguous identification of chemoattractants.